Facilitating conditions and Perceived Security as antecedents of trust among E-banking customers in Nigeria - Salimon, Maruf Gbadebo; Mohd Mokhtar, Sany Sanuri; Yusoff, Rushami Zien; Adeleke, A.Q.; Morakinyo, Saka (2017)
The purpose of this paper is to empirically discuss facilitating conditions and perceived security as major factors that influence trust among e-banking customers in Nigeria.In doing so, final data that were collected from 266 customers were analyzed using PLS-SEM (2.0).The results of the study show that facilitating conditions and perceived security significantly and positively influenced trust among the e-banking users of four major banks in Nigeria. Theoretical and practical implications of the study are presented as a guide for both academics and practitioners